KOMPARASI KINERJA KEUANGAN DENGAN TINGKAT KESEHATAN BANK DITINJAU DARI CAR, ROA, DAN LDR PADA PT.BANK BRI DAN PT.BANK BNI - Andi Hasryningsih Asfar; Lindawati Ayu (LP2M Universitas Bina Bangsa, 2023)
The soundness level of a bank is a comprehensive description of its financial performance which involves several critical aspects. This analysis does not only look at the extent to which a bank is able to maintain its financial stability, but also evaluates its capacity to deal with risks that may arise. The purpose of this study is to compare the financial performance of PT. Bank Rakyat Indonesia (Persero) Tbk with PT. Bank Negara Indonesia (Persero) Tbk. for the 2019-2022 period using the Capital Adequacy Ratio (CAR), Return On Assets (ROA), and Loan to Deposit Ratio (LDR). This research method is comparative qualitative. The type of data used is secondary data in the form of annual financial reports. Data analysis techniques by collecting data, reviewing the data obtained, calculating and analyzing it then interpreting it so that a real picture is obtained. The conclusions of the study are (1) CAR BRI and BRI are ranked 1 which means very healthy. This indicates that the two banks have a better level of capital adequacy to protect themselves from credit risk and other risks and the bank has greater ability to deal with unfavorable market conditions. (2) BRI's ROA was 2.99% higher than BNI's which reached 1.7%. This means that BRI is in a very healthy category compared to BNI which is in a healthy category. (3) The Loan to Deposit Ratio (LDR) of BRI and BNI shows that the two banks experience erratic increases and decreases every year, however, in terms of accumulation, BRI has a lower LDR than BNI. BRI's health level is in rank 2 in the healthy category, while BNI is in rank 3 in the fairly healthy category